2014
DOI: 10.1088/2041-8205/785/2/l27
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating the Progenitor Type of Supernova Remnants With Iron K-Shell Emission

Abstract: Supernova remnants (SNRs) retain crucial information about both their parent explosion and circumstellar material left behind by their progenitor. However, the complexity of the interaction between supernova ejecta and ambient medium often blurs this information, and it is not uncommon for the basic progenitor type (Ia or core-collapse) of well-studied remnants to remain uncertain. Here we present a powerful new observational diagnostic to discriminate between progenitor types and constrain the ambient medium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
190
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 164 publications
(215 citation statements)
references
References 52 publications
23
190
1
1
Order By: Relevance
“…With the resolution of pn and the statistics in our hand, it is not possible to resolve the K-shell lines from various Fe ions, which will become possible with next-generation X-ray calorimeters onboard Astro-H (Takahashi et al 2012) or Athena (Barret et al 2013). Yamaguchi et al (2014) used Suzaku to systematically search for Fe K emission from Galactic and LMC SNRs. Fe Kα emission was detected in 23 SNRs, including seven remnants in the LMC.…”
Section: Update On the Monitoring Of Snr 1987amentioning
confidence: 99%
See 2 more Smart Citations
“…With the resolution of pn and the statistics in our hand, it is not possible to resolve the K-shell lines from various Fe ions, which will become possible with next-generation X-ray calorimeters onboard Astro-H (Takahashi et al 2012) or Athena (Barret et al 2013). Yamaguchi et al (2014) used Suzaku to systematically search for Fe K emission from Galactic and LMC SNRs. Fe Kα emission was detected in 23 SNRs, including seven remnants in the LMC.…”
Section: Update On the Monitoring Of Snr 1987amentioning
confidence: 99%
“…Because the Fe K blend is a promising typing tool, we extended the search for Fe K emission of Yamaguchi et al (2014) to all LMC SNRs observed with XMM-Newton. Compared to the Suzaku sample, the coverage is more complete (i.e.…”
Section: Fe K Emission From Lmc Snrsmentioning
confidence: 99%
See 1 more Smart Citation
“…This SNR has long been suspected to be a cavity explosion, and its bulk dynamics are hard to interpret without a fast, sustained outflow from the progenitor, with properties similar to those of accretion winds (Badenes et al, 2007;Williams et al, 2011). Yamaguchi et al (2014), plus DEM L71 (Maggi et al, 2016). The shaded regions represent theoretical predictions from Type Ia SNR models interacting with a uniform interstellar medium (Badenes et al, 2003(Badenes et al, , 2005: orange for the 56 Ni-poor delayed detonation model DDTg, blue for bright 56 Ni-rich delayed detonation model DDTa.…”
Section: Type Ia Snr -Progenitor Connectionsmentioning
confidence: 99%
“…Patnaude et al (2015) modeled the circumstellar environments of core collapse progenitors for a range of mass loss rates and wind velocities, but did not consider Yamaguchi et al (2014). The transparent shaded regions correspond to models for either Ia or CCSNe ejecta, with yellow and light blue corresponding to the Ia models DDTa and DDTg, and red, green, magenta, and dark blue corresponding to CCSNe models SN 1987A, SN 1993J, and a 12 and 25M solar metallicity progenitor, respectively.…”
Section: Snr Bulk Propertiesmentioning
confidence: 99%